EFL Public Speaking Class Anxiety at STKIP PGRI Banjarmasin - Aulia, Vivi (Jo-ELT (Journal of English Language Teaching) Fakultas Pendidikan Bahasa & Seni Prodi Pendidikan Bahasa Inggris IKIP, 2022)
Public speaking was a crucial activity that involved the act of making a speech in front of audience. When the students were required to deliver their speech in front of others, they may face a more difficult situation. This frequently results in anxiety where people experience the fear of giving public speeches. This research aimed to investigate the level of EFL students’ public speaking anxiety (PSA) at STKIP PGRI Banjarmasin and how they used their individual efforts or strategy to reduce their PSA. This research was conducted with a mixed method design. There were 16 EFL students investigated using the Public Speaking Class Anxiety Scale (PSCAS) questionnaire and interview after they passed a Public Speaking course during a semester. The results of this research revealed some important findings. First, most EFL students have a high level of PSA. Next, most of them feel that they are afraid of making mistakes when they were performing public speaking in class. The third, the main factor causing them to have PSA was the feeling that they were afraid of having negative evaluations from the teachers and their classmates after performing the public speaking activity. Finally, they usually practice with friends beyond the class as one of their individual efforts to reduce their PSA. The conclusion of this research showed that the majority of EFL students’ PSA at STKIP PGRI Banjarmasin was at a high level and working with friends was the most individual effort they usually made to reduce their PSA.